Complications and Management of Glaucoma Surgery - Mahar, Prof. P. S. (Pakistan Journal of Ophthalmology, 2011)
Despite major advances in the development of novel drugs and laser techniques for intraocular pressure (IOP) reduction in eyes with glaucoma, a significant proportion of glaucoma patients ultimately require surgery to achieve target pressure. Trabeculectomy (Trab) still remains the gold standard in management of uncontrolled glaucoma. Many studies have compared initial trab versus medical treatment and confirmed trab providing consistently low IOP1,2. Other potential advantages of this surgical procedure include stabilization of IOP without any diurnal fluctuation, less reliance on patient’s compliance and cost effectiveness, which is of great significance in our present socio-economic environment.